Desain Fasilitas Publik Toilet Sebagai Penunjang Wisata di Pulau Lancang, Kabupaten Administrasi Kepulauan Seribu - Permata, Suciati (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2024)
The Thousand Islands is an administrative district in Jakarta Province, comprising a cluster of islands accessible by regular ferry routes from Muara Angke and Marina Ancol. Lancang Besar Island, one of the inhabited islands, has been the site of community service initiatives by the Architecture Department of Mercu Buana University since 2021. The first and second phases of the project involved the development of public infrastructure, including playgrounds, teacher offices, and community halls, all managed autonomously by the Al Hijrah Foundation without charging any fees to students. In the 2024 academic year, the project will progress with the design of public restroom facilities to enhance the island's tourism potential. These facilities are intended to address the needs of visitors while contributing to the improvement of the island's environmental quality. This initiative is in line with the broader tourism development strategy for the Thousand Islands, aiming to stimulate the local economy through the creation of functional and aesthetically cohesive infrastructure.